Struggling with the state I am in: Researching policy failures and the English National Health Service. (February 2021) - Lorne, Colin
Abstract: This article examines the tensions between failing when researching policy and researching policy that itself will inevitably tend towards failure. Putting geographic scholarship on policy mobilities into dialogue with recent attempts to reclaim academic failure, I discuss the emotional struggles that can punctuate the geographies of researching, mobilising and critiquing public policy. Supported by diary material as a fixed-term contract policy researcher studying health and care reforms in England, I reflect on failure when working within and beyond the spaces of the local state. With growing pressure on academics to impact policymaking, I emphasise the unsettling 'betweenness' of policy mobilities researchers unable to get to grips with power whilst becoming attached to, and part of, policies under investigation. Consequently, I suggest precarious academic researchers are, in more ways than one, occupying uncertain positions within accelerated worlds of fast policy as public intermediaries unable to talk about failure. The article concludes by outlining why this matters in the present crisis. Highlights: Examines the tensions between failing when researching policy and researching policy that itself will tend towards failure. Emotional struggles punctuate the geographies of researching, mobilising and critiquing public policy. Policy researchers can struggle to get to grips with state power whilst becoming attached to policies under investigation. Precarious policy researchers are occupying uncertain positions as intermediaries unable to talk publicly about failure. Emotions are integral to the growing pressures of fast policy research within the neoliberal academy.